Faculty of Management Science and Informatics - Vladimir Jamrich (Communications - Scientific letters of the University of Zilina, 2003)
The Faculty of Management at the University of Žilina was established in July 1990 as a result of a decision by the Academic Senate. In 1993 a new branch Management and Information Systems was created and in 1996 the name of the Faculty changed to the Faculty of Management Science and Informatics (FMSI). This name more precisely reflects the importance of information technology in the profile and orientation of the Faculty.The Faculty primarily specializes in managing activities in extensive systems. These include problems of managing and optimizing the transfer of products, passengers and information, as well as the designing of integrated interactive information systems for decision making support including economic connections and technical background.